(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article explores the critical shift from physical prototypes to virtual twins in robotics, emphasizing how virtualization—supported by rigorous mathematical models and advanced software—has become essential for overcoming traditional challenges like cost, safety, and development speed. The authors outline key formalisms, including kinematics, dynamics, control theory, and behavioral models, and highlight their practical implementation in modern, web-native software architectures. Emerging technologies like WebAssembly and WebGPU are enabling high-performance, browser-based simulations, democratizing robotics tools for education, prototyping, and remote testing. Case studies demonstrate real-world applications, from beginner programming to industrial robotics collaboration. The article also anticipates future advancements, such as integrating AI and formal methods to enhance simulation realism, train intelligent agents, and ensure system safety. Ultimately, the authors argue that refining virtual modeling techniques will accelerate the development of more capable, reliable robots, further embedding robotics into everyday life.